Phonological Interpretation of Consonants in the Russian Language in Borrowings at the Junction of Prefix and Root - A. A. Sokolyanskiy (Tsentr nauchnykh i obrazovatelnykh proektov, 2020)
The article is devoted to the phonological interpretation of consonants at the junction of prefix and root in borrowings such as Russian ir-ratsionalnyy, ir-realnyy, in-novatsiya, im-moralnyy, etc. The work is performed taking into account the typology of long and short consonant opposition in different languages of the world. The broad phonological context of the use of long and short consonants in the Russian language is taken into account, but due to the limited volume of the article, illustrations and interpretations of a number of phenomena are given in a generalized form. The author proceeds from the concept of multilevel phonology, developed by him in a number of works. In general, the description is based on primary phonemes that correspond to the phonemes of the Saint Petersburg Phonological School. It is shown that when identifying the morphemic structure of words such as irratsionalnyy one should proceed not from the spelling appearance, but from the accepted pronunciation. With this approach, the morphemic division of the previously cited words takes the following form: i-rationalnyy, i-realnyy, i-novatsiya, i-moralnyy, etc. Thus, the article deals with the problem of creating a phonological description in the conditions of orthoepic uncertainty and variability using a specific example.